Exploring the Role of Television Stations on Agribusiness in Kampala Central, Uganda. - Bappayo, Abubakar; Baba, Mustapha Abdulhamid; Maidunoma, Zannah (NIU Journal of Humanities, 2018)
The study was to investigate the impact of television coverage on agribusiness in Kampala central, Uganda. The objective of the study was to verify the effectiveness of television programs in promoting agribusiness in Kampala central, Uganda. The study employed descriptive survey design. The target population was 1,507,154 participants. The sample size was computed to 400 respondents using Solven’s formula. The participants included community members from Kampala central division and UBC TV, Bukedde TV, NTV, NBS TV, and Urban TV. The main research instrument was questionnaires. The study found that effectiveness of television programs in promoting agribusiness was satisfactory (overall average mean=3.69, Std=1.088). The study concluded that televised agribusiness programmes are effective in disseminating information to the farmers given their audio and video capabilities and disseminate information across the countryside about modern farming system in terms of hybrid seeds, off-seasonal vegetables, selection of seeds, and marketing of the agricultural products. The following recommendations were made: the need for television programs to increase agribusiness programs in their airing, the need for the televisions to increase the coverage of airtime allocated for agribusiness programs, the need for the government to support the television stations in their agribusiness programs, there is need for the government to organize practical training programs for the local farmers so that they gain practical skills because the information disseminated on televisions shows is not enough to the farmers, Similarly, journalists can as well involve the participation of the local leaders and district leaders so as to make the farmers even more cooperative.